Early-orogenic deformation in the Ionian zone of the Hellenides: Effects of slab retreat and arching on syn-orogenic stress evolution. (July 2019) - Tavani, S.; Corradetti, A.; De Matteis, M.; Iannace, A.; Mazzoli, S.; Castelluccio, A.; Spanos, D.; Parente, M.
Abstract: In this work we report on early-orogenic fracture patterns affecting a Cretaceous to Eocene sedimentary succession exposed in western Greece. These rocks belong to the Cenozoic External Hellenides, which form the western portion of the Aegean orocline. The analysis of fracture type, orientation, and crosscutting relationships provides constraints on the stress and strain patterns during the early stages of orocline formation. The fracture patterns in the study area includes early-orogenic extensional fractures arranged into two mutually orthogonal sets. These developed during progressive burial in the forebulge-foredeep system, ahead of the advancing compressive front. Tectonic solution seams at a high angle to bedding postdate these extensional structures. Solution seams are arranged in different sets, oblique to each other, and developed in the early stages of thrusting and folding. Extensional structures and solution seams are oblique to each other. Their orientation and crosscutting relationships provide evidence for clockwise vertical axis rotation of stress directions with time. This is consistent with the progressive arching of the forebulge-thrust belt system during progressive slab retreat. Highlights: We present fracture data from the Ionian zone of the External Hellenides. Fractures developed during early orogenic extension and layer parallel shortening. Horizontal extension and shortening are oblique to the trend of the belt. Fractures formed during bulge retreat and orocline development.